URGENSI NAHDLATUL ULAMA DALAM PEMERINTAHAN INDONESIA - Yovenska L. Man (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2018)
Abstract: As the largest Islamic mass organization in Indonesia, Nahdatul ulama certainly has enormous urgency in building a government in Indonesia. There are a lot of roles and services contributed by the ulema of the Indonesian state both in terms of social, political, educational and economic aspects. From the social side, the role of the ulama's ulema is seen as an effort to reaffirm all actual religious and social traditions that have institutionalized in a network of established structures and leadership patterns. From the political side, the ulema became the front guard's guard to maintain the integrity of the NKRI from a dangerous understanding. The journey of Nahdlatul Ulama, which initially had a lot of practical politics, then changed direction by focusing on religious social activities. In the world of education nahdatul uluma also contributes to the enormous service in educating Indonesian children, among others by establishing formal and informal educational institutions. In terms of the people's economy, the ulama took part in increasing the level of the economy of the Indonesian people with the establishment of shari'ah-based financial institutions. Keywords: Nahdlatul Ulama, Indonesian Government